Historical background of the development of liver transplantation in Russia - P. A. Ivanov (Трансплантология (Москва))
Transplantology is one of the objective indicators of development of both surgery and medicine as a whole in any country. In due time, it was Soviet scientists who became pioneers in experimental transplantology. Soviet surgeons' works made a great contribution to develop transplantology.